(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article is devoted to the problem of historical memory. The author considers the epic Manas as one of the important sources of the formation of the historical memory of the Kyrgyz.